2006
DOI: 10.1071/ea04068
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of feeding system and season on milk composition and Cheddar cheese yield in a subtropical environment

Abstract: Abstract. Milk obtained from cows on 2 subtropical dairy feeding systems were compared for their suitability for Cheddar cheese manufacture. Cheeses were made in a small-scale cheesemaking plant capable of making 2 blocks (about 2 kg each) of Cheddar cheese concurrently. Its repeatability was tested over 10 separate cheesemaking days with no significant differences being found between the 2 vats in cheesemaking parameters or cheese characteristics. In the feeding trial, 16 pairs of Holstein-Friesian cows were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The fat, DM, and lactic acid contents of cow milk samples were 3.05 to 4.20%, 11.71 to 13.21%, and 0.14 to 0.23%, respectively (Table 2). These results are consistent with the findings of Amenu et al (2006) and Ozrenk and Inci (2008). The differences in the composition of cow milk that was obtained at different lactation times may be related to the lactation period, feeding strategy of the cow, and feed composition (Fox and McSweeney, 1998).…”
Section: Composition Of Milksupporting
confidence: 91%
“…The fat, DM, and lactic acid contents of cow milk samples were 3.05 to 4.20%, 11.71 to 13.21%, and 0.14 to 0.23%, respectively (Table 2). These results are consistent with the findings of Amenu et al (2006) and Ozrenk and Inci (2008). The differences in the composition of cow milk that was obtained at different lactation times may be related to the lactation period, feeding strategy of the cow, and feed composition (Fox and McSweeney, 1998).…”
Section: Composition Of Milksupporting
confidence: 91%
“…In addition to the improved thermal stability of milk with high NPN content, the contribution of NPN to overall CP content may appear to be beneficial to producers operating within a CP payment scheme; however, this will result in milk of reduced protein quality or true protein content, which would be of particular concern to cheese manufacturers, as cheese yield is positively correlated with the true protein and casein contents of milk and negatively impacted by increased levels of NPN (Amenu et al., 2006).…”
Section: Impact Of Milk Composition On Dairy Product Functionalitymentioning
confidence: 99%
“…Thus, Galina et al (2007) have deduced that the cheese from grazing cows and goats was better in quality parameters for human nutrition than that produced from milk of indoor fed animals. Amenu et al (2006) found that cow's diet based on maize/barley silage and Lucerne hay reached higher milk yields and milk with higher protein than rain grown tropical grass pasture and oat diets. Cheese fat and cholesterol contents for grazing goats were lower than those contents obtained for indoor fed goats (Lucas et al 2008).…”
mentioning
confidence: 99%